Favipiravir for the treatment of coronavirus disease 2019 pneumonia; a propensity score-matched cohort study - Rand A. Alattar; Shiema Abdalla; Tasneem Abdallah; Rashid Kazman; Aseelah Qadmour; Tawheeda Ibrahim; Bassem Alhariri; Shahd H. Shaar; Abeer Bajwa; Abeir Alimam; Rabia Qazi; Fatma Ben Abid; et al. (Elsevier, 2022)
We retrospectively investigated the clinical outcomes of favipiravir in patients with COVID-19 pneumonia. Patients who between 23 May 2020 and 18 July 2020 received ≥ 24 h of favipiravir were assigned to the favipiravir group, while those who did not formed the non-favipiravir group. The primary outcome was 28-day clinical improvement, defined as two-category improvement from baseline on an 8-point ordinal scale. Propensity scores (PS) for favipiravir therapy were used for 1:1 matching. The unmatched cohort included 1493 patients, of which 51.7% were in the favipiravir group, and 48.3% were not receiving supplemental oxygen at baseline. Significant baseline differences between the two unmatched groups existed, but not between the PS-matched groups (N = 774). After PS-matching, there were no significant differences between the two groups in the proportion with 28-day clinical improvement (93.3% versus 92.8%, P 0.780), or 28-day all-cause mortality (2.1% versus 3.1%, P 0.360). Favipiravir was associated with more viral clearance by day 28 (79.8% versus 64.1%, P < 0.001). Adverse events were common in both groups, but the 93.9% were Grades 1-3. Favipiravir therapy for COVID-19 pneumonia is well tolerated but is not associated with an increased likelihood of clinical improvement or reduced all-cause mortality by 28 days.